Language and understanding - Kanjevac, Slobodan (Napredak, 2023)
The presentation begins with an overview of the language dealt with by the ancient philosophers at the time of considering the matters of logos. A special contribution to the topic of the “language” is recorded by the appearance of Plato and Aristotle, as well as by the broader and more profound interventions observed through verbum theology, rationalist and empiricist understanding of the language, analytical philosophy of the language, phenomenology as a postulation of philosophical hermeneutics. By entering that area, the language is further ontologically thematized as the “house of the being” or “the being that can be understood”.